Coping with food price volatility in ACP countries - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2012)
Price volatility can lead to rising import costs and local food market disruptions in ACP countries. These tend to hit the poorest households the hardest. Such fluctuations occurred in 2007, exacerbating malnutrition and triggering civil unrest. Yet, when a new period of instability occurred in 2010, experts attending a Brussels Development Briefing were able to recommend measures to limit price swings and mitigate their effects. These ‘Policy Pointers’ are central to this CTA Policy Brief. They include, in the short term: creating or restoring small-scale emergency food reserves, improving information systems on market data and setting up safety nets for vulnerable consumers and producers. In the longer term, it is important to promote increases in productivity, especially among smallholders.